TABLE OF CONTENTS AND LOCALIZATION OF RUBBER IN THE ROOTS OF KOK-SAGHYZ (Taraxacum kok-saghyz Rodin) - Kairat Rizabekovich Uteulin; Kabyl Zhambakin, Professor (Academic Journal of Physical and Chemical Sciences, 2020)
This article presents biological features, botanical description, and the results of the anatomical and physiological study of the Dandelion kok-saghyz (Taraxacum kok-saghyz Rodin), a valuable resource plant of world significance. Kok-saghyz is used as a technical culture, a source of high-quality rubber. Natural rubber is widely used in the rubber industry for the production of tires for automobiles, aircrafts, bicycles, as well as shoes, medical gloves and other products. The global rubber industry faces the real danger of the destruction of plantations of the main source of natural rubber - the rubber tree of hevea (Hevea brasiliensis), grown in the tropical humid climate of Southeast Asia, due to its diseases. This has happened in South America, which was originally a world center for the production of natural rubber; it has completely lost its position due to epiphytotics. There is currently a phytosanitary quarantine and a person who was accessed to hevea in South America should not visit the countries of Southeast Asia. Thus, there is a need for reserve additional plant species, the sources of natural rubber in the temperate zone, being adverse for acclimatization of hevea. Dandelion kok-saghyz is recognized as such a promising producer of natural rubber. According to data published, rubber of kok-saghyz sits in the latex vessels of the root, and the rubber content (6 to 14%) depends on the number of circles of the latex vessels (3 to 14). The number of circles of the latex vessels and, therefore, the rubber content in the roots depends on genotype, agricultural background and stage of kok-saghyz ontogenesis. The roots of kok-saghyz are known for high variability in the rubber content even in the same natural population of wild kok-saghyz from 0 to 47.87; 35.85 and 23.58% of the air-dry weight is due to several one-year covers in the root. Kok-saghyz is a highly polymorphic species that can be used in breeding programs. Individual selection provides for the high rubber content in the roots of kok-saghyz (10 to 14%). Currently, kok-saghyz is an important rubber plant with the following features: 1) high percentage of rubber; 2) flowering and fruiting in the first year of life; 3) high quality rubber. Kok-saghyz polymorphism provides for the selection of the most rubber-bearing and most precocious forms of this plant.